2015
DOI: 10.7287/peerj.preprints.1140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting cortical bone adaptation to axial loading in the mouse tibia

Abstract: The development of predictive mathematical models can contribute to a deeper understanding of the specific stages of bone mechanobiology and the process by which bone adapts to mechanical forces. The objective of this work was to predict, with spatial accuracy, cortical bone adaptation to mechanical load, in order to better understand the mechanical cues that might be driving adaptation. The axial tibial loading model was used to trigger cortical bone adaptation in C57BL/6 mice and provide relevant bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…But to what forces were the cells responding? Though mechanical stimulation used in this study was compressive in nature with respect to the entire tibia, the tissue-level strain at anterior medial face of the tibia, where the defect is located, has been shown, (12,47) and we have confirmed, to be tensile. Therefore, the vessel and collagen fiber alignment, as well as the cellular responses we observed in this study were presumably in response to this tensile force, though additional data are required for confirmation.…”
Section: Discussionmentioning
confidence: 62%
“…But to what forces were the cells responding? Though mechanical stimulation used in this study was compressive in nature with respect to the entire tibia, the tissue-level strain at anterior medial face of the tibia, where the defect is located, has been shown, (12,47) and we have confirmed, to be tensile. Therefore, the vessel and collagen fiber alignment, as well as the cellular responses we observed in this study were presumably in response to this tensile force, though additional data are required for confirmation.…”
Section: Discussionmentioning
confidence: 62%
“…An additional limitation of this study was that the micro-FE analysis did not take into account the component of frequency. Although our approach enabled us to link bone remodeling events to mechanical environments in vivo at the local level, the addition of theoretical models that incorporate cellular mechanosensing and intercellular communication [12,[35][36][37] will be highly useful to improve our understanding of the relationship between loading frequency and bone adaptation across multiple scales.…”
Section: Discussionmentioning
confidence: 99%
“…The presented DIC maps can further be used to validate FE models of the tibia loading in C57BL6/J mice, for example, examining the mechanical stimulus for bone adaptation. ( 24,35 ) Using DIC strain maps, we validated a FE model of the bone and correlated the mechanical stimuli to the ensuing spatial changes in osteogenic activity. ( 24 ) We found that fluid velocity predicts bone adaptation in adult bone both periosteally and endosteally, whereas strain energy density fails to predict endosteal bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the mechanical strains on cortical bone and its adaptation has been explored, particularly using the murine tibial–loading model, by comparing regions of bone formation from in vivo μCT, histology, and recently three‐dimensional fluorochrome mapping coupled with FE models of mechanical stimulus. ( 24,29–35 ) Although comparison of bone adaptation across these studies is challenging because they do not all report changes in the same morphological bone region, they have found that cortical bone in the young murine tibia is very responsive to loading, whereas controversial results have been found in aged bone. Some studies, which have used strain gauges to calibrate the applied load, found that aged bone does not exhibit efficient adaptation at similar strain magnitudes as young bone, interpreting this result as a failure of aged bone to adapt.…”
Section: Introductionmentioning
confidence: 99%